" The social conditions of Palestinian society and their impact on the increase in violence in the second decade of the 21st century " An applied study in the city of Ramallah – Palestine - Alawneh, Abdelmajid Nayif (Journal of Humanities & Social Sciences, 2020)
The study aimed to identify the effect of social background variables on the increase in the forms of violence that appear significantly in recent times within the Palestinian community. From various social groups within the Palestinian city of Ramallah, using the questionnaire tool to collect data and the method of simple random sampling. With regard to the results of this study, it has appeared that the most violent groups are young, male and people with Wii educational and lower monthly income and those with simple business. It also appeared that the economic and cultural causes are the most influencing the increase in the forms of violence within the Palestinian society, as they ranged between (88. 4%) and the ratio (82. 4%) for each of them respectively, followed by other reasons represented by social and psychological reasons, whose rates ranged Between (78. 1%) and (74. 1%), respectively. As for the places and times when forms of violence occur, it has appeared that they occur in some places, such as public streets, which have reached the percentage of (89. 6%) and some times such as free time, which have reached the rate of (86. 1%). There were also other negative effects resulting from the increase in the forms of violence, the majority of which was the increase in social problems, which reached a percentage of (87.7%). It was also found that the most prevalent forms of violence within the Palestinian society are verbal violence represented by torture and verbal assault on others directly, which came at a rate of (88.5%) and symbolic violence represented by indirect torture, either by word, hint or sign, which came with a rate of (80.7%). There was also a statistically significant relationship between the various variables of the social background studied here, including gender, age, marital status, number of family members, level of education, amount of monthly income, nature of work, degree of social problems such as unemployment, divorce, etc., and the increase in forms of violence within Palestinian society. It also appeared that there is an important, high and direct correlation between the increase in forms of violence and the increase in social problems in the sense that each of them increases with the increase of the other, and at the end of the research, a set of recommendations was developed at the public and private levels, the most important of which was the increased effectiveness of the role of social control bodies, especially the devices Formalities represented by the security services to reduce and limit the increase in the phenomenon of violence within the Palestinian society and work to care for proper education by parents and work to monitor their children and monitor their behaviours and friends and guide them towards their conduct of sound behaviour and act for him.